The Implementation of the 2013-Curriculum at Madrasah (Islamic School): A Case on Islamic Religious Education Subject - Nelli Murodah (Postgraduate Program, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aimed at describing the implementation of the 2013-curriculum at Madrasah. In this study, the researcher used a qualitative approach, where the data collection used were in-depth interviews, participatory observations, and documentation studies. The data were analyzed using an interactive analysis model proposed by Miles and Huberman. The results showed that the implementation of the 2013-curriculum in Islamic religious education subject at MAN (Islamic Senior High School) Insan Cendekia, Pekalongan employed three stages, i.e., planning, implementation, and assessment. In planning, teachers of Islamic religious education subject created and prepared lesson plans. Meanwhile, in the implementation, the teachers used a scientific approach that includes three stages, namely pre-activities, main activities, and post-activities. Meanwhile, in the assessment of learning, Islamic religious education teachers used authentic assessments as a benchmark for learning success at MAN Insan Cendekia Pekalongan. However, in the assessment format, there seems to be no uniformity. In addition, not all teachers carry out assessments promptly. It can be seen from the value leger that is still empty, which has not been filled by the teacher.